Sistem informasi berbasis komputer sebagai pendukung keputusan pemilihan pejabat menggunakan metode AHP - yahfizham yahfizham (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2014)
The issue of election officials to occupy a strategic position became the deep concern. It is common knowledge that if you want to become officers must spend some money, ethnicity, and proximity ("isms"). To avoid this, the solutions offered are software engineering (RPL / software engineering) with the help of computer-based information systems as decision support direct election of the method of AHP (Analytic Hierarchy Process). AHP method was applied to computer-based systems in particular to determine the official candidates who will occupy strategic positions in an organization. Election officials have to determine some criteria. The criteria are organized in a matrix form in pairswill then be tested for consistency using the formula . End result of the overall priority (global) ratings so you will know (rank) of each candidate's.Keyword :RPL (Software Engineering) dan AHP(Analytic Hierarchy Process)